Tailoring the structure of nanomaterials formed by light-induced synthesis - Astachov, Vladimir (2018)
A light is an energy portion that plays a very important role in nature. A light particle or photon can be absorbed, scattered or reflected. In some cases, light can greatly influence the formation of a crystal and guide its growth into hierarchical nano or microstructure.